2014
DOI: 10.3354/dao02698
|View full text |Cite
|
Sign up to set email alerts
|

Cyprinid herpesvirus-2 causing mass mortality in goldfish: applying electron microscopy to histological samples for diagnostic virology

Abstract: In June 2013, a major fish kill of adult goldfish Carassius auratus occurred in Runnemede Lake, New Jersey, USA: an estimated 3000 to 5000 fish died within ~5 d. Necropsy of 4 moribund fish revealed severely pale gills, and histopathology showed type I and II fusion of the gills, diffuse necrosis of hematopoietic tissue in anterior and posterior kidney, and multifocal necrosis of the spleen. Within necrotic areas, pyknosis and enlarged nuclei with marginalized chromatin were observed. Cyprinid herpesvirus-2, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The Cyprinivirus genus contains four species: three of them, cyprinid herpesvirus 1 (CyHV-1), cyprinid herpesvirus 2 (CyHV-2), and cyprinid herpesvirus 3 (CyHV-3), are associated with common carp or goldfish, while one of them, anguillid herpesvirus 1 (AngHV1), is associated with freshwater eels [127,128]. Cyprinid herpesviruses have been reported to cause serious mortality in common carp and crucian carp [129]. CyHV-1 is the cause of carp pox, CyHV-3 is fatal in carp and koi fish, and CyHV-2 is the etiological agent of herpesviral hematopoietic necrosis disease in common carp, goldfish, crucian carp, and gibel carp [130].…”
Section: Herpesvirus Genomesmentioning
confidence: 99%
“…The Cyprinivirus genus contains four species: three of them, cyprinid herpesvirus 1 (CyHV-1), cyprinid herpesvirus 2 (CyHV-2), and cyprinid herpesvirus 3 (CyHV-3), are associated with common carp or goldfish, while one of them, anguillid herpesvirus 1 (AngHV1), is associated with freshwater eels [127,128]. Cyprinid herpesviruses have been reported to cause serious mortality in common carp and crucian carp [129]. CyHV-1 is the cause of carp pox, CyHV-3 is fatal in carp and koi fish, and CyHV-2 is the etiological agent of herpesviral hematopoietic necrosis disease in common carp, goldfish, crucian carp, and gibel carp [130].…”
Section: Herpesvirus Genomesmentioning
confidence: 99%
“…In June 2013, a major fish kill of adult goldfish occurred in Runnemede Lake, NJ, USA: an estimated 3000− 5000 fish died within ~5 d, and the etiological agent was confirmed as CyHV-2 (Lovy & Friend 2014). Moreover, other recent studies have reported that mass mortalities caused by CyHV-2 infection occurred in Prussian carp Carassius gibelio in China (Wang et al 2012, Xu et al 2013) and the Czech Republic (Daněk et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to NJDFW diagnostic records, between 2007 and 2012, five documented cases of motile aeromonad septicaemia in various fish species in ponds and lakes within the state all occurred between April and May. Other mortality events in the spring may also be related to heavy infections with endemic parasites (Herman, ) and viral diseases (Lovy & Friend, ). Primary environmental factors that trigger these kills may be varied, although in the spring they are likely associated with abrupt warming of water temperature, poor body condition following overwintering and possibly other water quality factors such as pollution (Austin, ), which may all act to suppress the host immune system and make fish more susceptible to endemic infectious agents (Herman, ).…”
Section: Introductionmentioning
confidence: 99%